2015
DOI: 10.7852/jses.2015.53.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Development of processing technology for edible mature silkworm

Abstract: To increase the income of sericultural farms and expand sericulture industry, new high value-added products of sericulture which are beyond current products like 5th instar 3 day dried silkworm, male pupa and silkworm dongchunghacho are needed. For this sericulture product diversification, it is in desperate need of the edible processing method after 5th instar 4 day silkworm that silkgland formation is rapidly in progress during the larva periods. So far it was hard to eat because of silkgland formation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…In addition, the silkworm has recently received scientific attention and several studies have reported its health advantages against liver injury [16], Parkinson's disease [17], and diabetic hyperglycemia [18]. However, after the third day of the fifth instar, the protein composition of silkworm glands rapidly increases, hence, there is a problem insofar as the biological activity is lowered [19]. In addition, dried or refrigerated silkworms are difficult to consume as food because the silk protein is denatured to a high strength [19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the silkworm has recently received scientific attention and several studies have reported its health advantages against liver injury [16], Parkinson's disease [17], and diabetic hyperglycemia [18]. However, after the third day of the fifth instar, the protein composition of silkworm glands rapidly increases, hence, there is a problem insofar as the biological activity is lowered [19]. In addition, dried or refrigerated silkworms are difficult to consume as food because the silk protein is denatured to a high strength [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, after the third day of the fifth instar, the protein composition of silkworm glands rapidly increases, hence, there is a problem insofar as the biological activity is lowered [19]. In addition, dried or refrigerated silkworms are difficult to consume as food because the silk protein is denatured to a high strength [19]. Therefore, Ji et al have developed a new method of processing silkworms into an easy-to-eat form, in which the mature silkworms are steamed for 130 min at 100 • C before lyophilizing and grinding [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, after steamed at 100°C for 130 min using an electric pressure-free cooking machine (Kum Seong Ltd., Boocheon, Korea), mature silkworm larvae were freeze-dried with a freeze-drier (FDT-8612, Operon Ltd. Kimpo, Korea) at -50°C for 24 h. The freeze-dried silkworm larvae were pulverized twice using a hammer mill (HM001, Korean Pulverizing Machinery Co. LTD., Incheon, Korea) and a disk mill (Disk Mill01, Korean Pulverizing Machinery Co. LTD) sequentially (Ji et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…A among the representative edible insects in South Korea, Oxya chinensis sinuosa (Grasshopper) was also included (Ji et al, 2015). The protein concentration of Oxya chinensis sinuosa (Grasshopper) was about 742.8 g/kg dry weight, and it meant that edible insects were the valuable resource of dietary protein or of protein supplement (Kim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%